2013
DOI: 10.1124/mol.113.087080
|View full text |Cite
|
Sign up to set email alerts
|

Hits of a High-Throughput Screen Identify the Hydrophobic Pocket of Autotaxin/Lysophospholipase D As an Inhibitory Surface

Abstract: Autotaxin (ATX), a lysophospholipase D, plays an important role in cancer invasion, metastasis, tumor progression, tumorigenesis, neuropathic pain, fibrotic diseases, cholestatic pruritus, lymphocyte homing, and thrombotic diseases by producing the lipid mediator lysophosphatidic acid (LPA). A high-throughput screen of ATX inhibition using the lysophosphatidylcholine-like substrate fluorogenic substrate 3 (FS-3) and ∼10,000 compounds from the University of Cincinnati Drug Discovery Center identified several sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…However, unlike the competitive inhibitor HA155, which coordinates to zinc (PDB ID 2XRG), PAT-078 does not extend far enough to interact with the active site zincs, and thus is unable to inhibit cleavage of the nucleotidelike BNPP substrate. In support of this hypothesis, Fells et al (2013) have identified compounds that competitively inhibit cleavage of LPC-like substrates (LPC, FS-3), but also do not inhibit cleavage of nucleotide substrates. Molecular docking studies using these compounds identified a number of key interactions with ATX residues, including Leu214, Ala218, Phe275, and Tyr307, that correspond well with the ATX residues identified in this study (Fells et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, unlike the competitive inhibitor HA155, which coordinates to zinc (PDB ID 2XRG), PAT-078 does not extend far enough to interact with the active site zincs, and thus is unable to inhibit cleavage of the nucleotidelike BNPP substrate. In support of this hypothesis, Fells et al (2013) have identified compounds that competitively inhibit cleavage of LPC-like substrates (LPC, FS-3), but also do not inhibit cleavage of nucleotide substrates. Molecular docking studies using these compounds identified a number of key interactions with ATX residues, including Leu214, Ala218, Phe275, and Tyr307, that correspond well with the ATX residues identified in this study (Fells et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…In support of this hypothesis, Fells et al (2013) have identified compounds that competitively inhibit cleavage of LPC-like substrates (LPC, FS-3), but also do not inhibit cleavage of nucleotide substrates. Molecular docking studies using these compounds identified a number of key interactions with ATX residues, including Leu214, Ala218, Phe275, and Tyr307, that correspond well with the ATX residues identified in this study (Fells et al, 2013). Further, the authors predicted that these compounds bind in the hydrophobic pocket away from the zinc ions in a similar manner to PAT-078.…”
Section: Discussionmentioning
confidence: 73%
“…Binding of ATX ␣ to cellsurface HSPGs, via its polybasic insertion loop, represents an additional isoform-specifi c mechanism for spatially and temporally restricted LPA production. Precisely how ATX activity is regulated, what the structural determinants of and nucleotide products bound to ATX and ENPP1 suggest that many additional cores can be envisaged in the further development of inhibitors [see also ( 81 )]. The ATX inhibitors structurally characterized until now share common characteristics and explore the hydrophobic pocket with fl uoro-benzene and chloro-benzene moieties.…”
Section: Discussionmentioning
confidence: 99%
“…Further, additional analysis is needed to determine whether other pathway alterations may serve compensatory roles in the small set of patients with ENPP2 deletions. Together, these results indicate that the ATX/LPA signaling axis may be dysregulated in specifi c cancer subtypes, and that patients could potentially benefi t from targeted therapies blocking ATX/ LPA signaling Due to the pleiotropic connection of ATX in cancer pathology, considerable effort has been made to generate small molecule inhibitors that target its enzymatic activity ( 120,(164)(165)(166)(167)(168)(169)(170)(171)(172)(173). Using sensitive fl uorescence probes, such as TG-mTMP, Kawaguchi et al ( 174 ) identifi ed several novel ATX inhibitor scaffolds and solved the crystal structures of ATX-compound complexes at high resolution (1.75-1.95 Å).…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%